Perancangan Cetakan dan Simulasi Proses Manufaktur untuk Teknologi HPDC: Studi Kasus Produk Plakat - Komara, Asep Indra; Sidik, Barik; Hidayat, Ery; Wigenaputra, Dadan Heryada (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2024)
POLMAN Bandung plaque is a thick product with a relief shape on the surface of the product. The product was originally made using sand casting technology, but now it needs to be developed using high-pressure die casting (HPDC) molding technology. This process was hampered by the absence of technical documentation, so development started from the available sand-casting products. This development was carried out in two stages, first product design, and second tool design. Based on the results of the research carried out, an optimal HPDC design has been produced according to the desired specifications. Product designs are obtained through 3D scanning technology to obtain appropriate geometric data. Then the data generated for mold design and the HPDC process includes a specific casting pressure of 400 bar; casting locking force of 1311 kN; piston diameter of 40 mm; 31.6% fill rate; piston movement (V(x)): first phase 0.497 ms-1 to 307 mm, second phase 2.08 ms-1 to 390 mm. The analysis process in the shot-sleeve simulation has produced the right data for the production process so that machine control is more precise, effective, and efficient.